Lymphomyeloid organs of the Antarctic fish Trematomus nicolai and Chionodraco hamatus (Teleostei: Notothenioidea): A comparative histological study - ROMANO N; CECCARIGLIA S; MAZZINI M; MASTROLIA L.; ABELLI, Luigi (Polar Biology, 2000)
Lymphomyeloid organs of two common spe- cies of Antarctic fish, Trematomus nicolai and Chiono- draco hamatus, were studied with the aim of analysing some morphological aspects of these organs in relation to adaptation to low environmental temperature. The thymuses of T. nicolai and C. hamatus were flattened, incompletely lobated, with numerous Hassall-like bod- ies, which were mainly located in the central part of the organ in C. hamatus. In T. nicolai, thymocytes, erythroid and reticular epithelial cells filled the organ. In C. hamatus, the thymocytes intermingled with reticular epithelial cells were often close to groups of melano- macrophages. In both species, the thymus did not show distinct compartmentalisation; however, the thymocytes had significantly different sizes in the outer and inner portions of the thymus. The head kidney of both species was completely filled by haematopoietic tissue, highly vascularised and mainly lymphopoietic in T. nicolai, while both erythropoietic and lymphopoietic in C. hamatus. The spleen appeared mainly erythropoietic in T. nicolai and mainly lymphopoietic in C. hamatus. Solitary melano-macrophages in T. nicolai were close to numerous small vascular ellipsoids where erythroid and lymphoid cells were intermingled without the formation of red and white pulp areas. In C. hamatus, large lym- phoid areas were organised around the capillaries. The possible adaptation of lymphoid organs to the low temperature of polar water is discussed.